Analysis of default in the implementation of the Aceh health insurance program agreement - Salsabila, Fathya; -, Susiana (Geuthèë Institute, Aceh, 2024)
The implementation of the Aceh Health Insurance program is contained in the Cooperation Agreement between the Government of Aceh and BPJS Health so that the provisions of Article 1338 of the Criminal Code apply. However, in its implementation there is a delay in payment. The purpose of writing this thesis is to explain the factors causing default in the payment of Aceh Health Insurance contributions, efforts to resolve defaults in the implementation of the Aceh Health Insurance program agreement, and obstacles faced in resolving defaults between the Government of Aceh and BPJS Health in the implementation of the Aceh Health Insurance program agreement. The method used in writing this thesis is empirical juridical method with qualitative analysis. Based on the results of the research, the factors causing default in the late payment of Aceh Health Insurance contributions are due to a mismatch between the amount of the budget set and the amount needed within one year. Efforts made to resolve the default are to carry out budget efficiency to be transferred to Aceh Health Insurance contributions in APBA Amendments in 2023 and to prevent delays the Aceh Government has proposed a budget for Aceh Health Insurance contributions in 2024 according to needs. The obstacles faced in resolving defaults are the insufficient budget available in the 2023 DPA and delays in the APBA Amendment implementation process.